2020
DOI: 10.1111/ijn.12892
|View full text |Cite
|
Sign up to set email alerts
|

Family caregivers' experiences of interaction with people with mild‐to‐moderate dementia in China: A qualitative study

Abstract: Aim: This study aimed to explore the experiences of family caregivers interacting with people with dementia.Background: A majority of people with mild-to-moderate dementia live at home with family caregivers. This interaction creates positive experiences and challenges for these caregivers.Design: Descriptive phenomenological qualitative inquiry guided this study.Methods: This qualitative study involved semi-structured interviews with the caregivers of people with mild-to-moderate dementia (n = 10). Data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
0
10
0
2
Order By: Relevance
“…Although significant correlation was established between cognitive function and well‐being of family caregivers, this association was not identified in the multiple linear regression analysis. Based on previous reports showing that the severity of dementia decreases the well‐being of family caregivers, we assumed a correlation between cognitive function and well‐being, 20, 21 an expectation that was not borne out by the results. Research on caregiver strain also showed the cognitive function to be correlated with caregiver strain with no significance in the regression model 50 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although significant correlation was established between cognitive function and well‐being of family caregivers, this association was not identified in the multiple linear regression analysis. Based on previous reports showing that the severity of dementia decreases the well‐being of family caregivers, we assumed a correlation between cognitive function and well‐being, 20, 21 an expectation that was not borne out by the results. Research on caregiver strain also showed the cognitive function to be correlated with caregiver strain with no significance in the regression model 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have indicated that the well‐being of family caregivers may be impacted by a range of important factors common among individuals suffering from dimentia 19–23 . It is also noteworthy that activity of daily living (ADL) was a considerable predictor of well‐being of caregivers; evidence from qualitative researches showed that basic ADL care experience (such as assisting with toileting, washing or handling a fall and managing behavioural problems) was negatively related to well‐being of family caregivers of people with dementia 19, 20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A qualitative study analyzed the experience of family caregivers for PwD in China [ 10 ]. The authors found that caregivers could positively interact with PwD by employing positive strategies, creating opportunities, and organizing meaningful activities [ 10 ]. Such methods are essential for maintaining harmonious family relationships.…”
Section: Related Workmentioning
confidence: 99%
“…Despite several recent studies documenting the prevalence rates of dementia in China and its impact on caregiver burden (Chen et al, 2016; Li et al, 2018; Zhao & Li, 2020), evidence regarding the day-to-day care needs of families coping with dementia remains very limited (Wang et al, 2018; Wang, Cheung, & Leung, 2019; Yang, Wu, et al, 2021). Therefore, how to strengthen the health care and social service systems to support aging in place and enhance the quality of life of families coping with dementia requires a better understanding of the needs of people living with dementia and their family caregivers (Wang et al, 2020; Yang, Ye, & Sun, 2021). In response to challenges posed by the rapid population aging, the Chinese government issued the “90-7-3” framework as a guiding principle for long-term care in which 90% of all older adults would age in place at home, 7% would receive residential care in the community; and the remaining 3% would be cared for in institutional settings (Wang & Wu, 2017; Wang, Cheung, & Leung, 2019).…”
Section: Introductionmentioning
confidence: 99%